Legal Status of Profession Waqf from a Positive legal Perspective in Indonesia - Dwi Putri Nirmala, Rindang; Adzantyassurya Qotrunnada, Amara Srie; Mahmada, Elya; Nida Tahaanii, Aanisah; Andhita Putri, Karin (Dinasti Research, 2024)
This research paper,